2021
DOI: 10.1080/26410397.2021.1893890
|View full text |Cite
|
Sign up to set email alerts
|

Muslim men’s perceptions and attitudes on family planning: a qualitative study in Wajir and Lamu counties in Kenya

Abstract: In patriarchal societies like Kenya, understanding men's perceptions and attitudes on family planning is critical given their decision-making roles that affect uptake of contraception. Yet, most programmes mainly target women as primary users of contraceptive methods since they bear the burden of pregnancy. However, women-focused approaches tend to overlook gender power dynamics within relationships, with men wielding excessive power that determines contraception use or non-use. A qualitative study involving f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
(56 reference statements)
3
7
0
Order By: Relevance
“…Given that traditional gender roles where husbands are the main decision-makers are still very prominent among Muslims in Nigeria, heterogenous couples that are Indigenous / Other Religions and Muslim are less likely to engage in spousal communication than Christians. This is consistent with results from previous studies(Abdi, et al, 2021).4.2 Children Ever BornParticipants associated with African Indigenous Religions had the highest CEB, followed by Muslims and then Christians. Previous studies across Sub-Saharan Africa show the same trend.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Given that traditional gender roles where husbands are the main decision-makers are still very prominent among Muslims in Nigeria, heterogenous couples that are Indigenous / Other Religions and Muslim are less likely to engage in spousal communication than Christians. This is consistent with results from previous studies(Abdi, et al, 2021).4.2 Children Ever BornParticipants associated with African Indigenous Religions had the highest CEB, followed by Muslims and then Christians. Previous studies across Sub-Saharan Africa show the same trend.…”
supporting
confidence: 92%
“…Adebowale & Palamuleni (2015) also attributed women's empowerment to low fertility as more empowered women have more decision-making authority including decisions on contraceptive use, therefore reducing fertility. However, fertility is higher among Muslims than non-Muslims which may relate to traditional patriarchal gender roles of Islam where men hold the authority and are the main decision-makers of the household (Abdi, et al, 2021). It was also observed that women in the lower wealth quintile who wanted more children after having five children were three times as those in the richest quintile.…”
Section: Fertility Desiresmentioning
confidence: 98%
“…Although male condoms were mostly preferred, some participants expressed their interest and preference for using natural methods such as withdrawal. As documented in the previous study conducted in Wajir and Lamu counties in Kenya, men prefer withdrawal possibly because such a method is free from side effects and costs (Abdi et al, 2021). From the current study, it appears that men have limited choices of postpartum family planning methods, which this challenge could promote pregnancy during the postpartum period.…”
Section: Discussionsupporting
confidence: 51%
“…From the current study, it appears that men have limited choices of postpartum family planning methods, which this challenge could promote pregnancy during the postpartum period. Contrary to previous studies, vasectomy as one of the postpartum family planning methods are often inaccessible and most of the participants had less desire to use such services (Abdi et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“… 48 One study from Lamu and Wajir counties noted that religious beliefs, in particular, explained large family sizes. 49 In this paper, we analysed data from both in-depth interviews (IDIs) and focus group discussions (FGDs) with nomadic and semi-nomadic women and men of different ages, living in North Eastern Kenya. Drawing on our formative qualitative research, we explore: (1) gender and social norms around child spacing and modern FP, (2) family size preferences, and (3) how these approaches to spacing relate to local and global approaches to FP.…”
Section: Introductionmentioning
confidence: 99%